Palynology of the Muaradzi sub-basin, Moatize-Minjova Coal Basin, Karoo Supergroup, Mozambique - Pereira, Zelia; Manuel Carvalho Fernandes, Paulo; Lopes, Gilda; Marques, Joao; Vaz, Maria; Costa, Marta; Correia, Joao; Castro, Ligia; Galasso, Francesca (Review of Palaeobotany and Palynology, 2019)
The detailed palynostratigraphic study of four boreholes in the Muaradzi sub-basin, Moatize-Minjova Coal Basin (MMCB) southeast of Moatize, allowed the assignment of relative ages to the stratigraphic units. Three assemblages were studied in detail and are assigned to the Lopingian. Assemblage L1 is characterized by the rich occurrence of Guttulapollenites and Weylandites. Assemblage L2 is defined on the first occurrence (FO) of abundant Thymospora pseudothiessenii together with Indotriradites niger, Kraeuselisporites spp., Polypodiisporites mutabilis and Polypodiidites sp. Assemblage L3 is characterized by the first occurrence of Osmundacidites senectus together with the taxa described from the previous assemblages. Palynological correlation with other Karoo basins is discussed and three distinct palynostratigraphic events emerge based on the FO and abundance of key taxa (as for instance, FO of G. hannonicus, T pseudothiensenii and O. senectus). A close palynological correlation between Mozambique (Moatize-Minjova Basin), Tanzania (Selous Basin), Zambia (mid-Zambezi Basin) and Madagascar palynoevents is established. This major region can be assigned to the northern Karoo-aged basins of south-central Africa and the palynoevents can be correlated with Lopingian assemblages of Pakistan, India and some basins of East Antarctica. The southern Karoo-aged basins of south-central Africa, including South Africa and Zimbabwe, show different Lopingian palynoevents and a direct correlation is demanding. These palynological data may open new perspectives for coal exploration in the MMCB as the coal deposits show a wider stratigraphic distribution, reaching until the latest Lopingian. (C) 2019 Elsevier B.V. All rights reserved. project PALEOCLIMOZ [PTDC/CTA-GEO/30082/2017] info:eu-repo/semantics/publishedVersion